DATA-DRIVEN LOCATION STRATEGY: HOW AHP SUPPORTS EFFECTIVE RESTAURANT SITE SELECTION - Aji Rizky Hakim; Dina Dellyana (Journal of Social and Economics Research, 2025)
The rapid growth of the food and beverage (F&B) service industry in Indonesia has driven increasingly fierce competition, especially in the Greater Jakarta (Jabodetabek) area, which is home to nearly 40% of the nation's F&B service businesses. Therefore, location selection is a strategic decision that significantly determines a restaurant's success. Toko Bakmi Kita, established in Serang City in 2019, plans to expand its business reach to Jabodetabek area with a more measured and data-driven approach. This study aims to identify the key criteria for restaurant location selection using the Analytic Hierarchy Process (AHP) method and evaluate five alternative locations to determine expansion locations. Data was collected through interviews and AHP questionnaires with 15 business owners and professionals in the F&B service sector, as well as secondary data from Google Maps and MAPID. The results show that of the eight main criteria, accessibility is the most influential factor, followed by market attractiveness, rental costs, and customer flow drivers. At the sub-criteria level, distance to main roads, rental payment schemes, and daytime and nighttime occupancy rates are the main determinants of location attractiveness. Of the five locations analyzed, two had the highest scores: Graha Raya Tangerang (Location E) with a score of 88.56 and Grand Wisata Bekasi (Location A) with a score of 85.12. Both were deemed to best meet the combination of good access, market potential, and cost structure that support Toko Bakmi Kita's expansion in Jabodetabek area.